O Uso Dos Dispositivos Móveis No Ensino Da Língua Por-Tuguesa: Estímulo À Leitura E À Formação Crítica - Toyota, Lilian Moura [UNIFESP] (2017)
This research aims to discuss the relationship of the new technologies with reading in the process of teaching and learning Portuguese, from the use of Mobile Devices, which can make the classroom more dynamic, leading the student to acquire the habit of reading and interaction and, consequently, developing reading skill. The new Youth / Teen Generation is "connected" in the Net / Internet, as well as they know and dominate the different devices offered by the new technologies. On the other hand, school and society often say that this behavior among young people is a form of alienation from traditional content. According to UNESCO (2014), mobile technologies (Mobile Devices) can expand and enrich educational opportunities for students in diverse environments. For this study, interviews were conducted with open questions, with teachers from the public schools of the State Government of São Paulo, in the city of São Paulo. From the interviews, we analyzed the speeches of the teachers, observing the methodologies adopted by them in face of the new reality, and especially regarding the use of Mobile Devices in Portuguese classes to work with reading. It was observed that, although the technological resources are theoretically available to the teacher, in the analyzed cases, there is the teacher's lack of knowledge about digital technology and, above all, the non-use in the teaching and learning process. This strangeness occurs or because it does not have the Digital Literature necessary for the manipulation of the new technologies, or for the distrust on the devices technicians offered by them. The pedagogical discourse centered on the practice of rules and control by the teacher on the students prevents that it modifies the pedagogical roles in the school context, maintaining the centralizing and controlling figure, and letting pass the opportunity to be mediator of knowledge and propitiator of a reflexive and critical practice in different discursive genres on the internet. The study presented here is based on Koch (2009), Solé (1998), Silva (2011), Kleiman (2011, 2013) when dealing with the issues related to reading gender. For the authors, the reading goes beyond the barrier of the passive receiver, therefore, they require of the reader other skills that are beyond the act of reading. In parallel, the perspective of the Evolution of Educational Technology with the scholars Moran (2000) and Pierre Lévy (1999) and for the concepts on Digital Literature, the authors Red (2015), Braga (2007, 2013), Silva (2003) and Zacarias (2016) serve as a theoretical basis in this research, where one has to go beyond the use of the new technologies as a tool, but to understand how the language in the network happens and how the same language Influences people and the way to read a text. At the end of this research, it was possible to perceive that even the technology, in the case the Mobile Devices, is in the classroom, the use of this tool is not significant in comparison to the theory on the subject. The pedagogical discourse centered on authority and control does not allow the teacher to go through the unknown. We observe that this distrust is at the limit between knowing and not knowing, and that teacher training for the use of new technologies is essential for its pedagogical practice.